The Development of Art Teaching Activities, Visual Arts Using Harrow’s Teaching Model with Concept Map to Promote Oil Chalk Painting Skills of Grade 6 Students of Wat Klang School - Matong, Jutalak; Srisawad, Paranee; Kiatkheeree, Parussaya (Journal of Graduate MCU KhonKaen Campus, 2025)
The purposes of this research were 1) To develop teaching and learning activities for Art and Visual Arts using Harrow’s teaching and learning model and conceptual maps to promote students’ oil chalk coloring skills to be effective according to the criteria 80/80, 2) To compare the students’ oil pastel painting skills before and after the implementation of the instructional activities, 3) To compare the students’ academic achievement before and after the implementation of the instructional activities, and 4) To study the students’ satisfaction with the instructional activities using Harrow’s teaching model in combination with a concept map. The research sample were 20 students in grade 6 of Wat Klang School. The research instruments included learning management plan, achievement test, oil chalk gradation skill test, and satisfaction test. The basic statistics, such as percentage, mean, and standard deviation, were used to analyze the data. The research results found that the teaching and learning activities of the Art subject, Visual Arts, using Harrow’s teaching model with concept mapping to promote oil chalk painting skills were effective according to the criteria of 82.10/83.00. The students’ oil chalk painting skills after learning were significantly higher than before learning at .01. The learning achievement after learning was significantly higher than before learning at .01. The satisfaction with the learning management was at the highest level ( = 4.75, S.D.= 0.20).